Swimming and Sinking Behavior of Warm Water Pelagic Snails - Karakas, Ferhat; Wingate, Jordan; Blanco-Bercial, Leocadio; Maas, Amy E.; Murphy, David W. (Frontiers in Marine Science, 2020)
Swimming and sinking behavior by pelagic snails is poorly studied but is important in their ecology, predator-prey interactions, and vertical distributions. We used a low magnification, high speed stereophotogrammetry system to study the swimming and sinking kinematics of nine warm water pelagic snail species (seven thecosomes, one gymnosome, and one heteropod). As different thecosomatous pteropod species may have coiled, elongated, or globular shell morphologies, we focused on how the shell shape, body geometry, and body size affect their swimming behavior from a fluid mechanics perspective. In addition, ZooScan image analysis and metabarcoding of archived vertically stratified MOCNESS samples were used to relate swimming behaviors to night time and daytime vertical distributions. While different large scale swimming patterns were observed, all species exhibited small scale sawtooth swimming trajectories caused by reciprocal appendage flapping. Thecosome swimming and sinking behavior corresponded strongly with shell morphology and size, with the tiny coiled shell pteropods swimming and sinking the slowest, the large globular shelled pteropods swimming and sinking the fastest, and the medium-sized elongated shell pteropods swimming and sinking at intermediate speeds. However, the coiled shell species had the highest normalized swimming and sinking speeds, reaching swimming speeds of up to 45 body lengths s-1. The sinking trajectories of the coiled and elongated shell pteropods were nearly vertical, but globular shell pteropods use their hydrofoil-like shell to glide downwards at approximately 20° from the vertical, thus retarding their sinking rate. The swimming Reynolds number (Re) increased from the coiled shell species (Re ~ O(10)) to the elongated shell species (Re ~ O(100)) and again for the globular shell species (Re ~ O(1000)), suggesting that more recent lineages increased in size and altered shell morphology to access greater lift-to-drag ratios available at higher Re. Swimming speed does not correlate with the vertical extent of migration, emphasizing that other factors, likely including light, temperature, and predator and prey fields, influence this ecologically important trait. Size does play a role in structuring the vertical habitat, with larger individuals tending to live deeper in the water column, while within a species, larger individuals have deeper migrations.